Pengaruh Inflasi dan Pengangguran Terhadap Pertumbuhan Ekonomi di Indonesia - Fauzani Salsabila; Khairul Amri (Jurnal Ekonomi Manajemen dan Sekretari, 2023)
This research aims to determine the effect of inflation and unemployment on economic growth in Indonesia. Using annual time series data for the period 2000-2022, the analysis model used is multiple linear regression and autoregressive distribution lag (ARDL). This research reveals that there is no cointegration relationship between economic growth and inflation and unemployment. In both the long and short term, inflation has a positive impact on economic growth. Meanwhile, unemployment in both the long and short term has a negative impact on economic growth. These findings have implications that efforts to increase Indonesia's economic growth can be carried out through policy interventions related to the money supply which influences inflation and increases employment opportunities in order to reduce unemployment.